(Güney) Azerbaycan Millî Hükûmeti’nin toplumsal kökleri (1945-1946) - Rahmanifar, Mohammad (My University, 2023)
Yüzyıllar boyunca Azerbaycan bölgesi, çeşitli Türk hükûmetlerine başkentlik etmesinin yanı sıra her zaman özel bir ilgi merkezi olmştur. Bu ayrıcalıklı durum da ekonomik refahın beraberinde Azerbaycan merkezli bir zihniyetin oluşmasını sağlamıştır. XIX. yüzyıla gelindiğinde ise Güney Azerbaycan’ın elde ettiği merkeziyet ve göreli refahını kademeli olarak kaybetmesi ile adem-i merkeziyetçi eğilimler güçlenmiş ve “Meşrutiyet”, “Âzâdistân” gibi Tahran’ın merkezîliğine karşı çeşitli hareketler görülmeye başlanmıştır. Rızâ Şah döneminde uygulanan merkezci politikalar, Türkçenin yasaklanması, Güney Azerbaycan Türklerine yönelik sürdürülen ayrımcılık ve adaletsizlik, Güney Azerbaycan Türkleri arasında memnuniyetsizliğin artmasına ve İran’ın merkezî hükûmetinden uzaklaşma eğilimlerinin güçlenmesine yol açmıştır. II. Dünya Savaşı sırasında Müttefikler tarafından Rızâ Şah’ın devrilmesiyle Güney Azerbaycan Türkleri arasındaki siyasi hareketlilik yoğunlaşmış, nihayet 12 Aralık 1945’te Azerbaycan Millî Hükûmeti’nin kurulmasıyla süreç tamamlanmıştır. Azerbaycan Millî Hükûmeti, kuruluşunun ilk günlerinden itibaren Güney Azerbaycan halkının isteklerini yerine getirmeyi birinci önceliği olarak görmüştür. Bu çalışmada, Azerbaycan Millî Hükûmeti’nin tarihi, Güney Azerbaycan halkının isteklerini yerine getirme çabaları, yükselişinde ve yıkılışında bölgesel ve küresel güçlerin rolü incelenerek söz konusu hükûmetin toplumsal temellerine ve sosyal tabanına odaklanılmıştır.

Over the centuries, Azerbaijan has become the capital, or at least the center of special attention, of Turkic governments. This issue led to the formation of an Azerbaijan-centered mentality as well as economic prosperity. In the 19th century, as South Azerbaijan gradually lost its old centrality and relative prosperity, anti-Tehran tendencies became stronger and this process manifested itself in the form of movements against the centrality of Tehran, such as the Constitutional movement and the Azadistan movement. Reza Shah’s centrist policies and the prohibition of Turkic language, discrimination and injustice against South Azerbaijan Turks led to an increase in dissatisfaction among the South Azerbaijan Turks and the strengthening of anti-Tehran tendencies. With the overthrow of Reza Shah by the Allies during World War II, the political activity among the South Azerbaijan Turks intensified and finally on December 12, 1945, the Azerbaijan National Government was established. From the first days of its establishment, the Azerbaijan National Government has made it a priority to fulfill the wishes of the people of Southern Azerbaijan. In this research, in addition to studying the history of the National Government of Azerbaijan, its efforts to fulfill the aspirations of the people of South Azerbaijan, and the role of regional and global powers in the rise and fall of this government, we specifically focused on the social foundations and social base of this government.
Keywords: Adem-i merkeziyetçi eğilimler; Anti-centralism Tendencies; Azerbaijan; Azerbaijan National Government; Azerbaycan; Azerbaycan Millî Hükûmeti; Caucasus, South; Dış ilişkiler; Foreign relations; Güney Azerbaycan; Kafkasya, Güney; Politics and government; Siyaset ve yönetim; social base; Social structure; South Azerbaijan; Toplumsal taban; Toplumsal yapı; Turkic identity; Türk kimliği